Communication Generalities in International Theories - Bivol, Teodor (Acta Universitatis Danubius. Communicatio, 2022)
Communication is the process by which information and ideas are transmitted between people, organizations, or systems. It is a fundamental skill of human beings and plays a vital role in social interaction, mutual understanding and collaboration. Communication plays a vital role in an increasingly connected and interdependent world today. Effective communication is critical to building and maintaining interpersonal relationships. Through communication, people can make emotional connections, understand, and be understood by others. The ability to communicate openly and clearly can strengthen personal, family, work and social relationships. Adequate communication can help create a productive work environment, resolve conflicts and improve individual and team performance. Also, communicating through social media and other digital platforms offers limitless opportunities to convey information, create content, and connect with diverse audiences. Through communication, people can express options, analyze different perspectives and collaborate to find optimal solutions. The ability to communicate clearly, listen and negotiate can help resolve conflicts and reach consensus in different situations.